In hope of liberty : culture, community, and protest among northern free Blacks, 1700-1860 - Horton, James Oliver; Horton, Lois E. (Oxford University Press, 1997)
Covering the colonial period to the Civil War and spanning all of the northern United States, this text documents the antebellum northern black experience. In examining churches, schools, music, living arrangements, occupations, even the underground railroad, it demonstrates the central role of the black community in successfully managing the tensions born of assimilation and cultural difference. In the process, it shows the extensive national contributions of northern blacks.